Primary Generators of Visually Evoked Field Potentials Recorded in the Macaque Auditory Cortex - Kajikawa, Yoshinao (J Neurosci, 2017)
Prior studies have reported “local” field potential (LFP) responses to faces in the macaque auditory cortex and have suggested that such face-LFPs may be substrates of audiovisual integration. However, although field potentials (FPs) may reflect the synaptic currents of neurons near the recording electrode, due to the use of a distant reference electrode, they often reflect those of synaptic activity occurring in distant sites as well. Thus, FP recordings within a given brain region (e.g., auditory cortex) may be “contaminated” by activity generated elsewhere in the brain. To determine whether face responses are indeed generated within macaque auditory cortex, we recorded FPs and concomitant multiunit activity with linear array multielectrodes across auditory cortex in three macaques (one female), and applied current source density (CSD) analysis to the laminar FP profile. CSD analysis revealed no appreciable local generator contribution to the visual FP in auditory cortex, although we did note an increase in the amplitude of visual FP with cortical depth, suggesting that their generators are located below auditory cortex. In the underlying inferotemporal cortex, we found polarity inversions of the main visual FP components accompanied by robust CSD responses and large-amplitude multiunit activity. These results indicate that face-evoked FP responses in auditory cortex are not generated locally but are volume-conducted from other face-responsive regions. In broader terms, our results underscore the caution that, unless far-field contamination is removed, LFPs in general may reflect such “far-field” activity, in addition to, or in absence of, local synaptic responses. SIGNIFICANCE STATEMENT Field potentials (FPs) can index neuronal population activity that is not evident in action potentials. However, due to volume conduction, FPs may reflect activity in distant neurons superimposed upon that of neurons close to the recording electrode. This is problematic as the default assumption is that FPs originate from local activity, and thus are termed “local” (LFP). We examine this general problem in the context of previously reported face-evoked FPs in macaque auditory cortex. Our findings suggest that face-FPs are indeed generated in the underlying inferotemporal cortex and volume-conducted to the auditory cortex. The note of caution raised by these findings is of particular importance for studies that seek to assign FP/LFP recordings to specific cortical layers.